Analysis of Causes of Divorce in the Perspective of Islamic Law: A Case Study in the Class 1 A Religious Court of Padang - Adhha, Nurul (Universitas Islam Negeri Raden Intan Lampung, 2019)
This study analyzed in depth some of the factors that led to the divorces in Padang Community. The aim is to obtain a comprehensive understanding of the phenomenon as well as to find alternative solutions that can be used to anticipate/to prevent the occurrence of divorce. This study took place at Class 1 A Religious Court of Padang which is one of the institutions that deal with divorce issues. Based on existing data, from 2014 to 2016, divorce cases in the city of Padang showed quite high numbers. This study identifies three main factors that caused the divorce in the city of Padang; First, disharmony between partners, Second, disputes between partners, and third, no responsibility from one partner. These three factors, among others, have a significant role in the high percentage of divorce in the city.